PENINGKATAN KEWIRAUSAHAAN DALAM PENGOLAHAN PRODUK BAKSO IKAN PATIN - Khairani, Zulia; Soviyanti, Efrita; Kamilah, Faizah (Jurnal Pengabdian Kompetitif, 2023)
by the signing of MOU No. 025/FE/Ks/2022 concerning Cooperation in Implementing the Tri Dharma of Higher Education by the Dean of the Faculty of Economics and the Head of Rumbai Bukit Village. Based on the results of previous service activities regarding increasing mothers' knowledge about nutritious food for toddlers, information was found that one of the problems faced by the Rumbai Bukit sub-district was the problem of stunting in children. As a result of the excavation of natural potential in Rumbai Bukit, information was found that there is potential for cassava, papaya, oil palm, catfish, catfish, etc. Based on the completeness of food sources in the Rumbai Bukit sub-district, there should be no under-fives experiencing stunting in this sub-district. This service activity is a continuation of the previous service activity, namely about increasing entrepreneurship in processing catfish meatballs. Patin is a food source that is easy to obtain and at affordable prices in the Riau area, especially the Rumbai Bukit sub-district. The hope is that by increasing mothers' skills in processing nutritious food for children, stunting rates can be reduced and the community's welfare and economy can be improved. The results of this service activity found an increase in community knowledge and skills in processing products made from patin raw materials and as an idea for entrepreneurship Keywords: products, catfish, entrepreneurship